Implementing sustainability in the supply chain for small and medium-sized enterprises : green supply chain challenges in the German assembly industry - Ferber, Nicolas (2023)
Private individuals and the government have long since ceased to be the sole focus for ensuring a more responsible and sustainable society. Large companies are increasingly being held accountable to contribute and those who want to evade this can expect tremendous social pressure and consequently, there is an expanding body of research. However, there are still significant gaps regarding implementation for SMEs. Using a qualitative research method with eight semi-structured expert interviews from the German assembly industry and including existing literature, this research investigated the barriers SMEs face when implementing sustainability in their supply chain and the opportunities SMEs have to promote sustainability through their suppliers. In light of barriers to implementing sustainability, the thesis revealed that too high costs, too much effort, a lack of quality, and a lack of knowledge are the main internal barriers for SMEs, and regulations, social pressure, and dependencies on other companies as external barriers. In order to have an impact on other suppliers through the SMEs’ supply chain, SMEs are mainly limited in their size and associated purchase volumes. They can only have a limited impact through knowledge sharing and explicit selection of sustainable suppliers.